Mycogenic Synthesis of Extracellular Zinc Oxide Nanoparticles from Xylaria acuta and Its Nanoantibiotic Potential - Sumanth B (Dove Medical Press, 2020)
Basavaraju Sumanth,1,* Thimappa Ramachandrappa Lakshmeesha,1,* Mohammad Azam Ansari,2 Mohammad A Alzohairy,3 Arakere Chunchegowda Udayashankar,4 Balagangadharaswamy Shobha,1 Siddapura Ramachandrappa Niranjana,4 Chowdappa Srinivas,1,* Ahmad Almatroudi3 1Department of Microbiology & Biotechnology, Jnana Bharathi Campus, Bangalore University, Bangalore 560056, India; 2Department of Epidemic Disease Research, Institute for Research and Medical Consultations (IRMC), Imam Abdulrahaman Bin Faisal University, Dammam 31441, Saudi Arabia; 3Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Qassim 51431, Saudi Arabia; 4Department of Studies in Biotechnology, University of Mysore, Mysuru 570006, India*These authors contributed equally to this workCorrespondence: Chowdappa SrinivasDepartment of Microbiology & Biotechnology, Jnana Bharathi Campus, Bangalore University, Bangalore 560056, IndiaTel +91 9972091611Email srinivasbub@gmail.comAhmad AlmatroudiDepartment of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Qassim 51431, Saudi ArabiaEmail aamtrody@qu.edu.saPurpose: The study aimed to find an effective method for fungal-mediated synthesis of zinc oxide nanoparticles using endophytic fungal extracts and to evaluate the efficiency of synthesized ZnO NPs as antimicrobial and anticancerous agents.Methods: Zinc oxide nanoparticles (ZnO NPs) were produced from zinc nitrate hexahydrate with fungal filtrate by the combustion method. The spectroscopy and microscopy techniques, such as ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX), dynamic light scattering (DLS), and transmission electron microscopy (TEM) with selected area electron diffraction (SAED), were used to characterize the obtained product. Antibacterial activity on Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) samples was tested by broth microplate dilution technique. ZnO NPs antifungal activity was determined against plant pathogenic and regular contaminating fungi using the food-poison method. The anticancerous assay of the synthesized ZnO NPs was also investigated by cell uptake, MTT assay, and apoptosis assay.Results: The fungal synthesized ZnO NPs were pure, mainly hexagonal in shape and size range of 34– 55 nm. The biosynthesized ZnO NPs could proficiently inhibit both Gram-positive and Gram-negative bacteria. ZnO NPs synthesized from fungal extract exhibited antifungal activity in a dose-dependent manner with a high percentage of mycelial inhibition. The cell uptake analysis of ZnO NPs suggests that a significant amount of ZnO NPs (1 μg/mL) was internalized without disturbing cancer cells’ morphology. As a result, the synthesized ZnO NPs showed significant anticancer activity against cancer cells at 1 μg/mL concentration.Conclusion: This fungus-mediated synthesis of ZnO NPs is a simple, eco-friendly, and non-toxic method. Our results show that the synthesized ZnO NPs are an excellent novel antimicrobial and anticancer agent. Further studies are required to understand the mechanism of the antimicrobial, anticancerous action of ZnO NPs and their possible genotoxicity.Keywords: endophytic fungi, zinc oxide nanoparticles, antibacterial, antifungal, anticancerous